AH jump as predictor for successful Ablation of atrioventricular nodal reentrant tachycardia (AVNRT) - Al-Alwany, Ameen; Al-Saffar, Hilal B.; Mohammed, Najeeb H. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Atrioventricular nodal reentrant tachycardia (AVNRT) is the commonest regular supraventricular tachyarrhythmia. Ablation in the area of slow pathway (SP) has been successfully implemented in every day clinical electrophysiological practice for more than 20 years. Although the procedure is generally regarded as effective and safe, data on long-term effects and predictors of success or failure are incomplete.Objectives: This study was designated to prove that AH interval is an electrophysiological parameter which serves as a predictor for successful AVNRT ablation.Methods: While performing an electrophysiological study using a programmed atrial stimulation, thirty nine (39) patients (25 female and 14 males) with a mean age 51 ± 16.7 years with AVNRT were assessed and underwent AVNRT radiofrequency ablation using diagnostic and ablation catheters inserted via the right femoral veins. This study was performed during the period from February, 2013 to march, 2014 at the unit of Electrophysiogy in Leipzig heart center.Results: Acute successful AVNRT ablation was achieved in 39 (100%) patients, including 23 (59%) with slow pathway (SP) ablation and 16 (41%) with SP modification. Patients with SP modification were younger male, had faster AVNRT cycle length, and had more frequent isoproterenol usage before ablation. During six months follow-up period, all patients experienced no AVNRT recurrences. .Conclusions: AH jump served as predictor for successful Ablation of atrioventricular nodal reentrant tachycardia with a better outcome.